TINJAUAN HERMENEUTIKA GADAMERIAN TERHADAP PERGESERAN PARADIGMA TAFSIR PEREMPUAN DI INDONESIA - Abidin, Munirul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This research aims to find out the paradigm shifting of Qur’anic interpretation on woman verses from Gadamerian perspective. This writing finds out three paradigms: classical, modern and neomodernism paradigm. Each paradigm has its own world view that necessary to its context. From Gadamerian perspective, the emergence of those three paradigms in Qur’anic interpretation about woman verses is necessity. As a text, Qur’an is not a dead object, but it will be understood by people from different point of views. In interpreting a text, an instrument is used to help finding out the right interpretation. Interpretation is not a hall of mirrors in which interpreters only see themselves in different poses and shapes depending on the shape and angle of the mirror which confronts them. Rather, interpretation is a process of listening to others through their words and deeds.